Corporate criminals in the light of the problem of determining of the offender’s phenomenon - Пивоваров, В. В.; Барабаш, Т. Ю. (Theory and practice of jurisprudence, 2016)
This article deals with the problem of forming a new type of the offender called korporatyvist in the context of two conceptual approaches to the definition of corporate criminality. Proposed understanding of the person of the corporate criminals, ahead of concepts. A possibility of developing a typology of the offender - korporatyvist on the basis of a pluralistic hike to the definition of corporate criminality.